The Frequency of Hyperuricemia in Patients with Congestive Heart Failure (Medical Forum Monthly, 2022)
Objective: To find the frequency of hyperuricemia in patients with congestive heart failure.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of cardiology, Department of cardiology Qazi Hussain Ahmed Medical Institute Nowshera from 21st October, 2019 to 20th April, 2020.Materials and Methods: About 145 patients presenting with heart failure and raised uric acid level, with age more than 18 years and less than 60 years of either gender were studied. Serum uric acid level was measured in a specialized lab. Chi square test was applied with p < 0.05 as significant value.Results: Out of these 145 patients, 87 patients (60%) were male. “Among these 145 CHF patients, 93 patients (64.14%) were found to be hyperuricemic”. Out of these 93 hyperuricemic patients, 82.8% in hyperuricemic patients or 53.1% in total patients were males. “About 38 patients (40.86%) were in NYHA Class II, 25 patients (26.88%) were in NYHA Class III and 30 patients (52.25%) were in NYHA Class IV.”Conclusion: Raised serum uric acid level is associated with bad prognosis in patients with Heart Failure especially in male population